Syntax Unraveled : Exploring First Language Acquisition in Children's Linguistic Development - Meliana, Riska (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2024)
This study explores syntactic development in first language acquisition in 54-month-old children, focusing on children's linguistic ability to use conjunctions and relative phrases. A multilingual environment may influence syntactic development in these children differently compared to monolingual children. Multilingual children have a wider exposure to various syntactic structures, which allows them more flexibility in understanding and using these structures. Exposure to three languages can enrich the child's vocabulary and improve his/her ability to process linguistic information, which in turn affects the use of more complex syntactic structures. The findings from this study demonstrate the proficiency of a girl exposed to Bengkulu, Serawai and Indonesian languages. The child demonstrated a strong understanding of syntactic structures by scoring an average of 4.34 morphemes per utterance, which places the child's stage of language acquisition at stage V according to her age. This proficiency is likely due to the positive influence of a multilingual environment on the child's language development. This study underscores the importance of early exposure to multiple languages in enhancing syntactic proficiency and highlights the benefits of such exposure on children's language acquisition.